EDUKASI ALAT APD BAGI KESELAMATAN KERJA PADA PETUGAS KEBERSIHAN DI RSI KARAWANG - Jumaedi, Jumaedi; Darmawan, Wendi; Yuliana, Chaerani Tri; Muhidin, Muhidin; Widhianti, Wieke (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2024)
The use of personal protective equipment (PPE) is an essential measure in preventing workplace accidents, especially for cleaning staff in healthcare facilities who are at high risk of exposure to hazardous chemicals, infections, and sharp objects. This community service program aimed to improve the knowledge, attitudes, and behaviors of cleaning staff at RSI Karawang regarding the correct and standardized use of PPE. The activities included socialization, theoretical training, practical simulations, field monitoring, and evaluation through pre-tests and post-tests. The evaluation results showed a significant improvement in the knowledge and compliance of cleaning staff in using PPE after the program was implemented. This improvement was supported by interactive and comprehensive training methods, including discussions, simulations, and direct field monitoring. The program successfully achieved its main goal of creating a safer work environment and reducing workplace accident risks. It is hoped that this program can continue and be applied sustainably to enhance workplace safety at RSI Karawang